Contractual frameworks for collaborative innovation in Australian e-Research - Fitzgerald, B; Austin, A (2008)
The OAK Law Project ('OAK' standing for Open Access to Knowledge) is an Australian research project sponsored by the Queensland University of Technology and is funded by the Australian Federal Government's Department of Education, Science and Training. The OAK Law Project develops legal protocols and frameworks for managing copyright issues in an e-Research environment and analyses legal and other issues important to facilitating open access and e-Research in Australia and internationally. Presentation Paper - Focus: The Oak Law presentation will discuss and highlight: How legal processes and norms can frustrate innovative collaborative e-Research in the Australian context; How modified and streamlined legal frameworks and IP policies can be an assistance to innovative collaborative e-Research instead of being a barrier; The OAK Law 2007 survey's results and analysis into these issues; The Oak Law's 2008 submission on these issues to the Australian Federal Innovation Review; The findings of OAK Law's national innovation law working group on these issues from the May roundtable and issues presented or to be discussed at the group's September roundtable; The presentation will also provide examples of contractual and negotiation simplification methods which have arisen from the survey, the submission and the roundtables.